MENGETAHUI PENGARUH KINERJA ISLAM TERHADAP MOTIVASI ISLAM, KOMITMEN ISLAM, DAN PELATIHAN ISLAM PADA KARYAWAN PT. ASURANSI TAKAFUL KELUARGA DI JAKARTA - Yoga Dwi Anugrahadi; Ari Prasetyo (Universitas Airlangga, 2018)
The bacground of this research is that employees who work at Islamic FinancialInstitutions (IFIs) get problem both in quantitiy and quality of human resources. This study aims to analyse variables of human resource in Islamic perspective, such as Islamic motivation, Islamic commitment, Islamic training, and Islamic performance. This study used total 64 employees for random sampling observations and using Ordinary Least Square Regression analysis model with SPSS software. Data collection using questionnaire with Linkert scale 1 to 4.This study find partially that Islamic motivation and Islamic commitment are negatively related to Islamic performance, but Islamic training significantly related to Islamic performance. But, this research find that three variables simultanously related together to Islamic performance. Although Islamic training just has influence Islamic performance, therefore Islamic motivation and commitment have positive value in linier regression but in small value. REFERENCESAnwar Prabu Mangkunegara dan Abdul Waris. 2015. Effect of Training, Competence, and Discipline on Employee Performance in Company (Case Study in PT. Asuransi Bangun Askrida). 2nd Global Conference on Business and Social Science-2015, GCBSS-2015, 17-18 September 2015, Bali, Indonesia , 8.Rahman, Abdel Rahman AA. 1995. An Islamic Perpective On Organizational Motivation. The american journal of Islamic social science vol 12 no 2.Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung:Alfabeta.Suparyadi.2015. Manajemen Sumber Daya Manusia, Menciptakan Keunggulan Bersaing Berbasis SDM. Kediri:AndiTasmara, Toto. 2008. Membudayakan Etos Kerja Islami. Jakarta: Gema Insani.Zadjuli. 2004. Etika Sebagai Landasan Moral Pembangunan Ekonomi Di Indonesia.